CONTROLE DE UM MOTOR DE INDUÇÃO TRIFÁSICO UTILIZANDO A TÉCNICA VOLTS/HERTZ - Batista, Gilson R.; Campos, Mauricio d.; Tonielo, Edenilso; Ferreira, Augusto C. M.; Guisso, Ronaldo A. (Salão do Conhecimento, 2013)
Resumo